Educational Psychology: Patriotism and Educative Internalization through the National Anthem - Said Alwi; Muhammad Iqbal; Nur Hidayatul Nabihah (Mimbar Ilmu, 2023)
There are lots of songs, but they lack elements of patriotism and education. This deficiency makes the nation's structure fragile. Therefore, awareness and rethinking are needed to map and explain this to the public so that a sense of patriotism grows. This study aims to analyze and internalize the value mechanism of the Indonesia Raya song on the formation of the attitudes and character of Islamic boarding school students. This qualitative research uses the case study method at the leading pesantren. Data was collected through document studies and interviews. The data analysis technique uses descriptive qualitative analysis. This research has found that the internalization of patriotic values in the Indonesia Raya song can shape the attitudes and character of Islamic boarding school students. The internalization model of patriotism involves gradually educating song lyrics, understanding through assignments, and singing songs together. Educators and parents need to choose a national anthem that is appropriate for children's age and interests, understand the lyrics' meaning in depth, and make it a habit to sing the national anthem in their daily activities. Internalizing these values can produce young people who have a strong love for the motherland and care for the nation and state. Research on the internalization of patriotism and educational values through the national anthem has positive implications for education and the formation of national character.